The Effect of Pre Order Online Sales to Company Profits on PT. Aventama Hervent Solusindo Bandung - Tiris Sudrartono (Syntax Corporation Indonesia, 2020)
This research aims to find out how online pre order sales and profit earning on PT Aventama, also how big is the effect of pre order online sales towards the profit on PT Aventama, and to get to know about what are the efforts that could be able to do for increase the company profits through online pre order sales. Theory that supports in this research was revealed by Oki Pamungkas, 2018 who said that online sales is conducting sales activities from looking for potential buyers to offering products or goods by utilizing the internet network that is supported by a set of electronic devices as a link to the internet network, while Toto Prihadi 2012 said that profit is a measure of company's performance obtained from the results of reduction results of sales minus production costs. From conducted research, it can be obtained of the results of online pre order sales and company profits on PT Aventama, it's obtained results of 77.2% for online pre order sales and 35.7% for the profits and are categorized well. Then the correlation test is used for find out about the effect of online pre order sales with the results obtained at 84%, this value can be interpreted that the effect of online pre order sales to profits is very strong, while the other 16% is effected by other factors that it’s not examined by the author. Based on a simple linear regression analysis obtained Y '= 3.307 + 0.420X it means every online pre order sale is improved, it will be followed by an improve in company profit of 0.420 at a constant 3.037. With this research, it's expected that there will be a change in the company's profit through increasing online pre-order sales by creating advertisements, providing more complete ready stock products, and adding new suppliers so that the ordering process of products is faster to consumers